Adiponectin Related Vascular and Cardiac Benefits in Obesity: Is There a Role for an Epigenetically Regulated Mechanism? - Fontanella, Rosaria Anna; Scisciola, Lucia; Rizzo, Maria Rosaria; Surina, Surina; Sardu, Celestino; Marfella, Raffaele; Paolisso, Giuseppe; Barbieri, Michelangela (Frontiers in Cardiovascular Medicine, 2021)
In obesity, several epigenetic modifications, including histones remodeling, DNA methylation, and microRNAs could accumulate and determine increased expression of inflammatory molecules, the adipokines, that in turn might induce or accelerate the onset and development of cardiovascular and metabolic disorders. In order to better clarify the potential epigenetic mechanisms underlying the modulation of inflammatory response by adipokines, the DNA methylation profile in peripheral leukocytes of the promoter region of IL-6 and NF-kB genes and plasma miRNA-21 levels were evaluated in 356 healthy subjects, using quantitative pyrosequencing-based analysis, and correlated with plasma adiponectin levels, body fat content and the primary pro-inflammatory markers. In addition, correlation analysis of DNA methylation profiles and miRNA-21 plasma levels with intima-media thickness , a surrogate marker for early atherosclerosis, left ventricular mass , left ventricular ejection fraction, and cardiac performance index, was also performed to evaluate any potential clinical implication in terms of cardiovascular outcome. Results achieved, confirmed the role of epigenetics in the obesity related cardiovascular complications and firstly supported the potential role of plasma miRNA-21 and IL-6 and NF-kB DNA methylation changes in nucleated blood cells as potential biomarkers for predicting cardiovascular risk in obesity. Furthermore, our results, showing a role of adiponectin in preventing epigenetic modification induced by increased adipose tissue content in obese subjects, provide new evidence of an additional mechanism underlying the anti-inflammatory properties and the cardiovascular benefits of adiponectin. The exact mechanisms underlying the obesity related epigenetic modifications found in the blood cells and whether similar epigenetic changes reflect adipose and myocardial tissue modifications need to be further investigated in future experiments.